Opposite roles of cannabinoid receptors 1 and 2 in hepatocarcinogenesis. Issue 10 (11th May 2016) - Suk, Ki-Tae; Mederacke, Ingmar; Gwak, Geum-Youn; Cho, Sung Won; Adeyemi, Adebowale; Friedman, Richard; Schwabe, Robert F
Abstract : Objective: The endocannabinoid system (ECS) exerts key roles in the development of liver fibrosis and fatty liver, two diseases that promote the development of hepatocellular carcinoma (HCC). Although cannabinoids exert potent antitumour effects in vitro, the contribution of the ECS to carcinogenesis in vivo remains elusive. Design: Expression of key components of the ECS, including endocannanabinoids, endocannabinoid-degrading enzymes and endocannabinoid receptors, was determined in healthy liver and tumours. Diethylnitrosamine-induced hepatocarcinogenesis was determined in mice deficient in fatty acid amide hydrolase (FAAH), the main anandamide (AEA)-degrading enzyme, in cannabinoid receptor (CB)1, CB2, or transient receptor potential cation channel subfamily V member 1 (TRPV1)-deficient mice. Results: Murine and human HCCs displayed activation of the ECS with strongly elevated expression of CB1 and CB2 but only moderately altered endocannabinoid levels. Contrary to the antitumour effects of cannabinoids in vitro, we observed increased hepatocarcinogenesis in FAAH-deficient mice, a mouse model with increased AEA levels. Accordingly, inactivation of CB1, the main receptor for AEA, in wild-type or FAAH-deficient mice suppressed hepatocarcinogenesis. In contrast, inactivation of CB2 increased hepatocarcinogenesis. CB1 was strongly expressed within HCC lesions and its inactivation suppressed proliferation and liver fibrosis. CB2 was predominantly expressed in macrophages. CB2 inactivation decreased the expression of T-cell-recruiting chemokines and inhibited hepatic T-cell recruitment including particular CD4+ T cells, a population with known antitumour effects in HCC. TRPV1 deletion did not alter HCC development. Conclusions: Similar to their role in fibrogenesis, CB1 and CB2 exert opposite effects on hepatocarcinogenesis and may provide novel therapeutic targets.